Virtual assistant in information management for integrated crop management [Asistente virtual en la gestión de la información para el manejo integrado de cultivos] - Mendo Jara, Jossemar Ross (2020)
ABSTRACT The lack of information on the part of the agricultural producer generates some inconveniences in communication, loss of time and money, that is why it is looking for another communication alternative. This article deals with the benefits of implementing a Virtual Assistant in information management for integrated crop management. This is a Quasi-Experimental investigation where the survey was used as a technique for collecting data from agricultural producers in the province of Otuzco and the documentary review. To prepare the Virtual Assistant, the XP methodology was used, which comprises the following stages: Planning, Design, implementation and testing. The results of this research is that with the implementation of the virtual assistant it influences the costs of access to information, reducing costs by up to 90%. In addition, it determines that 77.46% of agricultural producers agree with this process of obtaining information and, finally, it also influences the time since 1 day of 8 hours can be reduced to 15 minutes